Gender Composition of Editors and Editorial Boards in Seven Top Criminal Justice and Criminology Journals from 1985 to 2017. Issue 3 (3rd July 2019) - Cory Lowe, Clayton; A. Fagan, Abigail
Abstract: This paper examines the gender composition of editors and editorial board members of seven top criminal justice and criminology (CCJ) journals from 1985 through 2017. The findings indicate that women have historically been, and continue to be, underrepresented in these positions. From 1985 through 2017, women comprised 14% of all Editors-in-Chief, 27% of all Associate Editors, and 22% of all Editorial Board members. While there was a period during the early 2000s when Justice Quarterly and Criminology achieved gender parity in representation across all of the editorial roles, this equality was short lived. The other journals have never achieved gender parity, and, on average, women have comprised 3.8% to 35.2% of the editorial positions at each of the journals. The implications of this imbalance for women's scholarship and professional success are discussed, and recommendations for changes to CCJ journal policies and practices to ensure more equity are provided.